Pengaruh Kompensasi, Kompetensi, dan Motivasi melalui Teknologi Informasi terhadap Kinerja Koperasi Jasa Tirta Kencana - Adinda Ranandhea; Eddy Soegiarti K; Andi Indrawati (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
This study aims to analyze the influence of compensation, competence, and motivation on employee performance with information technology as a mediating variable at Koperasi Jasa Tirta Kencana Samarinda. The research employs a quantitative approach, collecting data through questionnaires distributed to 50 meter reader employees using saturated sampling technique. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 4.0 to examine variable relationships.The results indicate that competence has a significant positive effect on information technology, while compensation and motivation show no significant influence. On the other hand, compensation, competence, motivation, and information technology directly and significantly affect employee performance. Notably, information technology only serves as a significant mediator in the relationship between competence and performance, but not for compensation-performance or motivation-performance relationships.The study's implications highlight the importance of enhancing employee competence and optimizing information technology utilization to improve performance. Organizations are advised to reevaluate compensation policies and motivation strategies to more effectively promote technology adoption. Future research could expand variables or employ qualitative approaches to gain deeper insights.